Landmarks in English literature - Gaskell, Philip (Edinburgh University Press, 1998)
A comprehensive guide to writers and their works which helps people understand where the books they read belong in the history and development of literature, see how they work technically, and appreciate them more fully. This comprehensive survey of writers and their works gives you a 'good reading guide' of important books from Chaucer to T. S. Eliot, and clear explanations of the history and techniques of fiction, poetry and drama. Full of insights from the author's many years of teaching, the book ends with an appendix on creative writing as a way of learning about literature, and an annotated bibliography. This is an ideal first-stop for students, readers and adult learners needing an accessible and informed introduction to the joys of literature.